2002
DOI: 10.1097/00007632-200204010-00013
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Plane Correction in Idiopathic Scoliosis

Abstract: The Cotrel-Dubousset technique ensures considerable sagittal correction of the spine. In the course of scoliosis correction, it is possible to preserve the normal preoperative sagittal profile of the spine, to correct the slightly flattened thoracic kyphosis, to increase materially the kyphosis of the frankly hypokyphotic spine, to preserve or restore normal lumbar lordosis in a considerable percentage of the cases, to avoid angular segmental hyperlordosis at the level of the first disc below the fusion, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 20 publications
4
58
0
4
Order By: Relevance
“…However, consensus appears to exist in the necessity to restore a global spinal alignment in the sagittal plane while correcting the thoracic hypokyphosis [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, consensus appears to exist in the necessity to restore a global spinal alignment in the sagittal plane while correcting the thoracic hypokyphosis [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…7,27 Curve magnitude, points of fixation, selection of instrumented level, and especially curve flexibility have been reported to be of great importance. 22,32 Implant density is a focus of recent studies focuses due to the high economic cost and related complications.…”
mentioning
confidence: 99%
“…3, 10,16,38 Although most surgeons would agree that placing 2 pedicle screws at every level fused is usually unnecessary for coronal curve correction, 4,7,17,21,25 the optimal implant density remains unknown. Especially when the sagittal plane has to be taken into consideration, to the best of our knowledge, insufficient evidence of optimal implant density is available to help with decision making.…”
mentioning
confidence: 99%
“…In this study, they found that all patients with lumbar lordosis above 60 degrees were decreased postoperatively by about 20°. In other words, they demonstrated that high preoperative lordosis is a risk factor for more loss of postoperative lordosis (21).…”
Section: Discussionmentioning
confidence: 99%